Associations between teacher-student relationship and externalizing problem behaviors among Chinese rural adolescent - Yang, Shuping; Zhu, Xingchen; Li, Wencan; Zhao, Haohan (Frontiers in Psychology, 2023)
The primary objective of this study is to present a fresh perspective on the correlation between teacher-student relationships and externalizing problem behaviors among adolescents. While previous research has examined this connection, there is still an insufficient understanding of the underlying mechanisms. Moreover, the crucial role of peer relationships, mental health, and parental knowledge has been overlooked. In this study, a total of 6919 Chinese rural adolescents aged 13-19 years participated by completing an anonymous self-report questionnaire. The results show that: (1) teacher-student relationship has a protective effect against the development of externalizing problem behaviors; (2) peer relationship and mental health both have a mediating role in the relationship between teacher-student relationship and externalizing problem behaviors; (3) teacher-student relationship can indirectly affect externalizing problem behaviors through the chain mediation of peer relationship and mental health; (4) parental knowledge plays a moderating role between the teacher-student relationship and externalizing problem behaviors. As the level of parental knowledge increases among rural adolescents, the impact of the teacher-student relationship on externalizing problem behaviors becomes more pronounced; and (5) the impact of teacher-student relationship on externalizing problem behaviors has no significant gender differences. Given the study's empirical outcomes, we discuss potential explanations and advocate for a comprehensive pedagogical approach to mitigate rural adolescent externalizing behaviors. This entails nurturing teacher-student relations, fostering inclusive peer environments, emphasizing mental health literacy, and synergizing with caregivers for a holistic home-school intervention.